The relationship between UVT and turbidity, with respect to the disinfection of surface waters - Roussillon, Guillaume (Cranfield University, 2009)
UV transmittance (UVT) is a parameter very closely related to the efficiency of any UV processes. Firstly a theoretical model of UVT proposed by Gregory (2006) was assessed and secondly an experimental approach was undertaken to find out any relationship between turbidity and UVT. UVT calculations were made for a range of particle diameter from 100nm to 5µm and to assess the impact of particle characteristics (particle size, particle number concentration and refractive index) on UVT. The theoretical model showed that the most important parameter affecting UVT was particle size and this was attenuated when the refractive index of the particle was small. The sensitivity of turbidity measurement required to show a 1% variation in UVT for UVT (for UVT above 90%) was calculated to be 0.01NTU which is below the level of sensitivity of most commercial system. Experiments with made solution containing one pollutant showed that turbidity is linearly related to the UVT (turbidity range between 0.14-5 NTU), but for real and non commercial water compositions UVT cannot be estimated using turbidity measurement. The nature of turbidity cannot be directly related to the particle characteristics which are particle size, chemical composition and hence absorbance and scattering coefficient. Finally from comparison between experimental results and theoretical calculation of UVT it appears that difference in UVT prediction (given values from 0% to 100% of UVT whereas measurement are between 90-99%) was mainly due to an error in theoretical determination of particle number concentration measurement. As an improvement of the theoretical model it was proposed to calculate the particle number concentration from 4 size particle fractionated solutions and then these solutions were diluted and UVT calculations and measurement were performed. Difference between predicted and measured UVT was still too important (but lower than 4%) to get a good correlation and use the theoretical model as a tool to predict UVT.
Keywords: UV processes; particle size; UVT; scattering coefficient; concentration measurement; pollutant